The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1002/hep.510290142
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of electrogenic anion secretion in normal and cystic fibrosis gallbladder mucosa

Abstract: Fluid and ion transport across biliary epithelium contributes to bile flow. Alterations of this function may explain hepatobiliary complications in cystic fibrosis (CF). We investigated electrogenic anion transport across intact non-CF and CF human gallbladder mucosa in Ussing-type chambers. In non-CF tissues, baseline transmural potential difference (PD), short-circuit current (Isc), and resistance (R) were ؊2.2 ؎ 0.3 mV (lumen negative), 40.7 ؎ 7.8 A/cm 2 , and 66.5 ؎ 9.6 ⍀ · cm 2 , respectively (n ‫؍‬ 14). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
42
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 57 publications
3
42
0
Order By: Relevance
“…39 Alternatively, ATP8B1 defect could affect the transcriptional activity not only of FXR, 13 but also of other transcription factors, like HNF1, which regulate the tissue-specific expression of CFTR. 40 Because CFTR is a major determinant of hydroelectrolytic secretion in the biliary tract, 20,[41][42][43] CFTR downregulation may contribute to impaired bile secretion through bile inspissation in PFIC1. This would explain the typical ultrastructural abnormality of bile in PFIC1 termed "Byler bile", characterized by a coarsely granular appearance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Alternatively, ATP8B1 defect could affect the transcriptional activity not only of FXR, 13 but also of other transcription factors, like HNF1, which regulate the tissue-specific expression of CFTR. 40 Because CFTR is a major determinant of hydroelectrolytic secretion in the biliary tract, 20,[41][42][43] CFTR downregulation may contribute to impaired bile secretion through bile inspissation in PFIC1. This would explain the typical ultrastructural abnormality of bile in PFIC1 termed "Byler bile", characterized by a coarsely granular appearance.…”
Section: Discussionmentioning
confidence: 99%
“…This may impair the contribution of cholangiocytes to bile secretion and also potentially explain some of the extrahepatic manifestations in PFIC1 and related disorders. The gallbladder, a site of high endogenous expression of ATP8B1 and of CFTR, 20,21,42 fully takes part to the regulation of the bile acid pool, 46 and thus may be of particular importance in the pathogenenesis of PFIC1.…”
Section: Discussionmentioning
confidence: 99%
“…Purinergic nucleotides are present in bile in concentrations sufficient to activate purinergic receptors. 54 Stimulation of these receptors may promote anion transport both in biliary 18,21,22 and pancreatic 55 duct epithelial cells, at least transiently. 19,20 Interestingly, ATP stimulated HCO 3 Ϫ secretion only in the presence of elevated intracellular cAMP as previously shown.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to cAMP-stimulated Cl Ϫ channels, Ca 2ϩ -activated Cl Ϫ conductances have also been described in both murine 19,20 and human biliary epithelial cells, 21,22 but their relationship to HCO 3 Ϫ secretion and their function in CFTR-deficient cells are unknown. We studied these relationships in both control and CFTR-deficient human bile duct cells.…”
mentioning
confidence: 99%
“…High levels of CFTR mRNA have been shown to exist in the human and mouse gallbladder epithelium (5,34,35). In addition, non-CF human gallbladder epithelia have been shown to produce cAMP-inducible electrogenic Cl 2 secretion that is absent in CF tissues (36,37). Functional studies on ferret and pig CF and normal gallbladder epithelia have yet to be reported.…”
mentioning
confidence: 99%